2018
DOI: 10.1302/1863-2548.12.170204
|View full text |Cite
|
Sign up to set email alerts
|

MRI in idiopathic, stable, slipped capital femoral epiphysis: Evaluation of contralateral pre-slip

Abstract: Abstract:PurposeEarly diagnosis and treatment of slipped capital femoral epiphysis (SCFE) is important to prevent slip progression and avoid complications. We sought to determine if MRI findings in patients with unilateral SCFE could indicate ‘pre-slip’ or predict future SCFE in the contralateral hip.MethodsA prospective study evaluated patients with unilateral SCFE over a two-year period. MRI of the asymptomatic hip was performed within the perioperative period. Patients were followed with radiographs until a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…A previous study sought to utilize MRI to evaluate contralateral SCFE upon presentation. 7 This study enrolled 33 patients from 2011 to 2013. In this study, six of 33 patients had positive MRI findings suggestive of a pre-slip.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study sought to utilize MRI to evaluate contralateral SCFE upon presentation. 7 This study enrolled 33 patients from 2011 to 2013. In this study, six of 33 patients had positive MRI findings suggestive of a pre-slip.…”
Section: Resultsmentioning
confidence: 99%
“…Many parameters have been proposed as predictive factors for contralateral, sequential SCFE including: skeletal maturity, 5 body mass index (BMI) 6 and magnetic resonance imaging (MRI) pre-slip parameters. 7 Femoral head/neck morphology, especially the posterior sloping of the epiphysis, has also been implicated. 8 - 10 Previous studies have shown that the posterior sloping angle (PSA) of the physis on an axial radiograph is significantly higher in patients who progress to contralateral, sequential SCFE.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, surgeons favored select measurements and frequently utilized advanced imaging. MRI, the most popular alternative among survey participants, 23 and CT scans 24 have been suggested in many studies as adjuncts or alternatives to standard radiography, which remains the first choice for SCFE. However, from this survey, it cannot be determined whether surgeons commonly order advanced imaging in practice or if they would like to consider MRI and CT as an alternative or supplement to radiographs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty five percent of SCFE are bilateral. 13,14,15,16 Suspect SCFE in an obese, adolescent boy during the rapid growth spurt that has hip, thigh, or knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…14 Although MRI still has limited use in making the diagnosis of SCFE, small studies indicate MRI may be useful in determining if an occult or pre-slip is present in the contralateral hip with a sensitivity of 80% and a specificity of 92%. 15,16 Thus, once the diagnosis of SCFE is made, the patient should not bear any…”
Section: Significant Findingsmentioning
confidence: 99%